Dissociated Response in Metastatic Cancer: An Atypical Pattern Brought Into the Spotlight With Immunotherapy - Humbert, Olivier; Chardin, David (Frontiers in Oncology, 2020)
When evaluating metastatic tumour response to systemic therapies, dissociated re-sponse is defined as the coexistence of responding and non-responding lesions within the same patient. Although commonly observed on interim whole-body imag-ing, the current response criteria in solid cancer do not consider this evolutive pat-tern, which is, by default, assimilated to progression. With targeted therapies and chemotherapies, dissociated response is observed with different frequencies, depending on the primary cancer type, treatment, and imaging modality. Because FDG PET/CT can easily assess response on a lesion-by-lesion basis, thus quickly revealing response heterogeneity, a PET/CT dissociated re-sponse has been described in up to 58% of women treated for a metastatic breast cancer. Although some studies have underlined a specific prognostic of dissociated response, it has always ended up being described as an unfavourable prognostic pattern and therefore assimilated to the “Progressive Disease” category of RE-CIST/PERCIST. This dichotomous imaging report (response vs progression) pro-vides a simple information for clinical decision-support, which probably explains the relatively low consideration for the dissociated response pattern to chemotherapies and targeted therapies until now. With immune checkpoint inhibitors, this paradigm is quickly changing. Dissociated response is observed in around 10% of advanced lung cancer patients and appears to be associated to treatment efficiency. Indeed, for this subset of patients, a clinical benefit of immunotherapy and favourable prognosis are usually observed. This spe-cific pattern should therefore be considered in the future immunotherapy-adapted criteria for response evaluation using CT and PET/CT, and specific clinical man-agements should be evaluated for this response pattern.